1974
DOI: 10.1073/pnas.71.9.3542
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Murine Leukemia Virus Production in Chronically Infected AKR Cells: A Novel Effect of Interferon

Abstract: Treatment of AKR cells that had spontaneously become producers of a murine leukemia virus with a partially purified mouse interferon (> 5 X 107 international mouse reference units per mg of protein)inhibited endogenous virus production. This inhibitory effect decreased over a 72-hr period in a manner similar to interferon-induced antiviral activity diiected against vesicular stomatitis virus in AKR cells. Despite the inhibitory effect of interferon on infectious murine leukemia virus and viral reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
2

Year Published

1977
1977
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 9 publications
7
45
2
Order By: Relevance
“…A similar effect of IF was observed when measured in terms of reverse transcriptase, infectivity or physical virus particles. This finding is consistent with that of Friedman & Ramseur (1974). However, Pitha et aL (i 976) found IF had a much greater effect on the infectivity of the released virions than on their reverse transcriptase activity.…”
Section: Discussionsupporting
confidence: 80%
“…A similar effect of IF was observed when measured in terms of reverse transcriptase, infectivity or physical virus particles. This finding is consistent with that of Friedman & Ramseur (1974). However, Pitha et aL (i 976) found IF had a much greater effect on the infectivity of the released virions than on their reverse transcriptase activity.…”
Section: Discussionsupporting
confidence: 80%
“…Interferon (IFN) inhibits murine leukaemia viruses (MuLV) at a late step in the virus productive process (Billiau et al, 1974;Friedman & Ramseur, 1974;Pitha et al, 1976;Billiau et al, 1975), while translation of virus proteins is apparently not affected. The inhibitory effect of IFN on these viruses can be expressed in one of two ways: (i) IFN caused a drastic reduction in the release of the virus particles from the cell membrane (Billiau et aL 1974;Friedman et al, 1975;Chang et al, 1977Chang et al, , 1978 and the budding virions were found to accumulate on the plasma membrane surface (Chang et al, 1977); or (ii) the effect of IFN was expressed as a dramatic reduction of the infectivity of the progeny virions, while the number of virions produced was only marginally reduced (Pitha et al, 1976;Wong et al, 1977).…”
Section: Interferon Induces the Production Of Membrane Protein-deficimentioning
confidence: 99%
“…Based on the results of previous studies, several laboratories have suggested that interferon treatment inhibits murine leukemia virus at a late stage(s) in virus replication (5)(6)(7)(8)(9)(10)(11). In view of the relationship between glycoproteins and intramembranous particles, the block of virus production by interferon may involve an alteration of membrane-associated glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…These changes could have been due either to interferon-induced alterations in the plasma membrane or to competition between interferon and the other ligands for a common binding site. In addition, interferon treatment of cells infected with RNA tumor viruses caused an unusual inhibition, which may be related to interferon-induced changes in the plasma membrane. In some systems, murine leukemia virus appeared to accumulate at the surface of interferon-treated cells (5,6); This resulted in a decreased production of the virus and an increase in the intracellular concentration of viral p30 antigen (7,8). In other systems, virus particle production in interferon-treated cells was quite close to that in untreated cells, but the infectivity of the particles was markedly decreased (9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation